Analysis of Job Changes in Poland Using the Bayesian Method - Grzenada, Wioletta (Zastosowanie metod bayesowskich do badania mobilności pracowniczej Polaków, 2011)
The primary objective of the work is to identify demographic and socio-economic factors influencing occupational mobility in Poland in the years 1950–1988. The career mobility has been modelled using a Bayesian Poisson regression model. Analysis of employment periods has been performed for three age groups. Moreover, in spite of the small size of the third age group, the Bayesian approach enabled result comparison for all age groups. In modelling the number of employment periods, the following determinants have been considered: the place of residence, sex, education level, the intention to continue education within two years, the intention to change place of residence within two years, having a family, the number of children, socio-occupational group and the age of entering workforce.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 102-122
Keywords: mobilność zawodowa; mobilność siły roboczej; occupational mobility; Poisson regression; bayesian models; population mobility; labour force mobility